Death Penalty Perspective in Malaysia in Theological Study of Christian Ethics - Dennis Gaie; Yusak Tanasyah (Journal of Religious and Socio-Cultural, 2023)
The Bible tells us that punishment is not a retribution, but punishment is needed to balance the situation resulting from a person’s evil deeds. In the Bible, God Himself teaches us to forgive one another. There are two views that support and those that oppose the death penalty. We should know that those who receive the death penalty are basically criminals who have committed horrible crimes and here the death penalty is retribution. As we know that God gives power to the government to punish anyone who commits evil, and the government delegates that power to someone or individuals (as a servant of God) to carry out the task of God’s punishment to those who commit evil. In Malaysia, the death penalty still applies to anyone found guilty of committing murder against a fellow human being. On the other hand, there are those who do not agree with the death penalty on the grounds that the death penalty is not effective in tackling crimes, and they are more in favor of a life sentence.